2015
DOI: 10.1016/j.tics.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Object processing in the infant: lessons from neuroscience

Abstract: Object identification is a fundamental cognitive capacity that forms the basis for more complex thought and behavior. The adult cortex is organized into functionally distinct visual object-processing pathways that mediate this ability. Insights into the origin of these pathways have begun to emerge through the use of neuroimaging techniques with infant populations. The outcome of this work supports the view that, from the early days of life, object-processing pathways are organized in a way that resembles that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Supporting this hypothesis, Wilcox and Biondi (2015) determined that babies of 4½ months of age can use shape differences between objects to individuate them, but not chromatic differences that become accessible towards 11½ months of age. Likewise, there is evidence that, up to at least 4 years of age, children do not develop an ability to establish extent similar to that of adults (Huttenlocher et al, 2002).…”
Section: State Non-conceptualism and Its Problemsmentioning
confidence: 96%
See 1 more Smart Citation
“…Supporting this hypothesis, Wilcox and Biondi (2015) determined that babies of 4½ months of age can use shape differences between objects to individuate them, but not chromatic differences that become accessible towards 11½ months of age. Likewise, there is evidence that, up to at least 4 years of age, children do not develop an ability to establish extent similar to that of adults (Huttenlocher et al, 2002).…”
Section: State Non-conceptualism and Its Problemsmentioning
confidence: 96%
“…In this fashion, Cohen and Strauss (1979) indicate that the first concepts would form around 30 weeks of age as a result of the discrimination of visual stimuli of female faces. In the same line, Wilcox and Biondi (2015) proposed that infants aged 3½ months show sensitivity to perceptual discontinuities in speed and path of motion and that 4½ months rely on the perception of shape differences to individuate objects. However, other concepts not linked to perception such as concepts about spatial relationships and object functions would emerge much later, when children are 10 months old (in the first case) (Horst et al, 2005) or two or more years of age (in the second case) (Mandler, 2008a;Rakison & Butterworth, 1998).…”
mentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/desc about what features objects should have when revealed (e.g., Kibbe & Leslie, 2011;Wilcox & Biondi, 2015;Xu & Carey, 1996). The present research explored individuation and identity tracking and examined the origins of these abilities in very young infants.…”
Section: Introductionmentioning
confidence: 98%
“…This expectation would depend on at least three abilities: (a) individuation , the ability to determine that two objects were in the box; (b) identity tracking , the ability to track these objects across events and hence predict that two objects would fall out of the box; and (c) re‐identification , the ability to specify what features these objects would have. Developmental research has shown that each of these abilities can pose difficulties for infants: Under certain conditions, infants fail to correctly individuate objects, they fail to correctly track objects from event to event, and they have limited expectations about what features objects should have when revealed (e.g., Kibbe & Leslie, ; Wilcox & Biondi, ; Xu & Carey, ). The present research explored individuation and identity tracking and examined the origins of these abilities in very young infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation